Peran British Council Dalam Kerja Sama Kebudayaan Inggris-Indonesia Melalui Program “Connections Through Culture” - Raharjo, Pramudya; Saraswati, Dini Putri (Universitas Medan Area, 2024)
This article examines the role of the British Council in facilitating cultural cooperation between the UK and Indonesia through the Connections Through Culture (CTC) program. The primary focus of the research is on how international artistic collaborations serve as a strategic medium for strengthening cross-cultural relations. The analysis reveals that the art projects initiated through CTC not only support the exchange of ideas and knowledge but also play a significant role in promoting the values of equality, diversity, and inclusion. This study contributes to a deeper understanding of cultural diplomacy, particularly in the context of non-state actors fostering global cultural networks. By highlighting how cultural cooperation concepts are applied in the British Council's initiatives, this article offers new insights into the role of non-state actors in building more inclusive and sustainable international relations.